Effects of Subacute Ammonia Nitrogen Stress on the Growth, Antioxidant Capability, and Immunity of Blunt Snout Bream (Megalobrama amblycephala) Juveniles - Xiangyang Yuan; Qian Wang; Mengyang Dai; Xinyu Xiong; Hengjie Wang; Canli Wang (Fishes)
To investigate the effects of subacute ammonia nitrogen stress on the growth, antioxidant capacity, and innate immunity of juvenile blunt snout bream (Megalobrama ambrycyphala), a sample of fish (average body weight 6.55 ± 0.24 g) was divided into three groups: a control group (G1), a 10% LC50 ammonia nitrogen stress group (G2), and a 20% LC50 ammonia nitrogen stress group (G3). The fish in G1 were reared in tap water with aeration. The fish in G2 were reared in water with 6.82 mg/L ammonium chloride at 10% LC50. The fish in G3 were reared in water with 13.64 mg/L ammonium chloride at 20% LC50. The feeding period was 4 weeks. Then, the growth, antioxidant, and immune response parameters of the fish were analyzed. The results showed that the median lethal concentration (LC50) of the ammonia nitrogen solution for blunt snout bream juveniles at 96 h was 68.18 mg/L. The final body weight, weight gain rate, specific growth rate (SGR), total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), albumin, globulin, acid phosphatase (ACP), and alkaline phosphatase (AKP) of fish in the stress groups were significantly lower than in the control group (p < 0.05); however, the MDA content of fish in the control group was significantly lower than that of those in the stress groups (p < 0.05). Furthermore, the relative expression levels of the GHRa, GHRb, IGF1, and IGF2 genes in the muscles of fish in the stress groups were significantly downregulated compared to the control group (p < 0.05). The relative expression levels of the SOD, CAT, Leap1, and Leap2 genes in the liver of fish in the stress groups were significantly lower than those in fish in the control group (p < 0.05). In conclusion, subacute ammonia nitrogen stress inhibited growth performance and decreased the antioxidant capacity and immunity of blunt snout bream.